Children’s Historical Literacy Improvement Program for The First Graders at Brawijaya Smart School - Nurhayani, Ika; Hariyanti, Rosana (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
This community service aimed to improve the historical literacy of the ﬁrst grade students at the Elementary School of BSS (Brawijaya Smart School) regarding the history of Malang. BSS Elementary School is located in Malang City, East Java. The community service activity consisted of writing and publishing a book about one of the cultural heritages of Malang, distributing it to the ﬁrst graders, and organizing a storytelling performance based on the book. The community service team chose the classical history displayed in the Jago Temple, built in the 13th century during the Singhasari period. The temple is located in Malang Regency. This activity received a good response from the homeroom teacher and the ﬁrst-grade students of the BSS elementary school. The students expressed their interest in learning more about the history of Malang. It can be concluded that this community service has been successful in improving the historical literacy of the students about their city.